2016
DOI: 10.1016/j.jacc.2016.08.033
|View full text |Cite
|
Sign up to set email alerts
|

Scar Homogenization Versus Limited-Substrate Ablation in Patients With Nonischemic Cardiomyopathy and Ventricular Tachycardia

Abstract: In patients with dilated nonischemic cardiomyopathy, scar-related VT, and evidence of low-voltage regions on electroanatomic mapping, endoepicardial homogenization of the scar significantly increased freedom from any recurrent ventricular arrhythmia compared with a standard limited-substrate ablation. However, the success rate with this approach appeared to be lower than previously reported with ischemic cardiomyopathy, presumably because of the septal and midmyocardial distribution of the scar in some patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
52
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(53 citation statements)
references
References 31 publications
0
52
0
1
Order By: Relevance
“…1 Endocardial, intramural, and epicardial scar provides the anatomical substrate that supports the maintenance of reentry VT. 2,3 Invasive endocardial electroanatomical mapping provides the ability to define the myocardial substrate to determine areas of low voltage as a surrogate for scar, to identify potential reentrant circuits and perform substrate-based ablations. 4,5 While an endocardial only ablation approach is often efficacious in patients with ischemic cardiomyopathy, 6 patients with nonischemic cardiomyopathy often have patchy intramural or epicardial scar that is an important substrate target for ablation. 7,8 Prior studies have shown that endocardial unipolar mapping can provide an adequate surrogate to define epicardial bipolar voltage, [9][10][11] and thus help the proceduralist determine whether an epicardial ablation strategy may be of value.…”
Section: Introductionmentioning
confidence: 99%
“…1 Endocardial, intramural, and epicardial scar provides the anatomical substrate that supports the maintenance of reentry VT. 2,3 Invasive endocardial electroanatomical mapping provides the ability to define the myocardial substrate to determine areas of low voltage as a surrogate for scar, to identify potential reentrant circuits and perform substrate-based ablations. 4,5 While an endocardial only ablation approach is often efficacious in patients with ischemic cardiomyopathy, 6 patients with nonischemic cardiomyopathy often have patchy intramural or epicardial scar that is an important substrate target for ablation. 7,8 Prior studies have shown that endocardial unipolar mapping can provide an adequate surrogate to define epicardial bipolar voltage, [9][10][11] and thus help the proceduralist determine whether an epicardial ablation strategy may be of value.…”
Section: Introductionmentioning
confidence: 99%
“…A detailed knowledge of the VT substrate is mandatory in this setting in order to identify the potential VT circuits and to delineate the optimal ablation strategy for each patient. VT ablation procedures are currently recognized as technically challenging with a non‐negligible risk of complications , and are usually associated with long ablation times due to the presence of multiple VT circuits or extense VT substrate that must be targeted . Traditionally, endocardial and/or epicardial mapping has been performed in a point‐by‐point fashion with a linear catheter incorporating a 3.5 mm distal electrode and a proximal 2 mm.…”
Section: Introductionmentioning
confidence: 99%
“…VT ablation procedures are currently recognized as technically challenging with a non-negligible risk of complications [5][6][7] , and are usually associated with long ablation times due to the presence of multiple VT circuits or extense VT substrate that must be targeted. 8,9 Traditionally, endocardial and/or epicardial mapping has been performed in a point-by-point fashion with a linear catheter incorporating a 3.5 mm distal electrode and a proximal 2 mm. electrode with a 2 mm interelectrode distance.…”
Section: Introductionmentioning
confidence: 99%
“…Limited ablation at a border zone that exhibits a pace-mapping match with extension into a dense scar (T-shaped lesion) were employed in SMASH VT,182 while more extensive linear lesions transecting the entire scar were proven effective in EURO VT(Figure 8-2) 183. More recently, extensive homogenization aimed to target all abnormal electrograms with low voltage has been shown to be more effective when compared to limited ablation strategies [184][185][186]. Extensive ablation strategies of scar during sinus rhythm are highly reliant on the accuracyF I G U R E 8 -1 Evolution of mapping systems with depiction of anteroapical scar from porcine validation of singlepoint mapping systems (CARTO) to higher resolution mapping with multielectrode acquisition in human (NavX) of low-voltage regions mapped, although electrogram signatures such as split high-frequency components and late potentials may be useful when differentiating scar from poor contact.…”
mentioning
confidence: 99%